2009
DOI: 10.3748/wjg.15.595
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of bispectral monitoring of conscious sedation during endoscopic mucosal dissection

Abstract: AIM:To assess the usefulness of bispectral index (BIS) monitoring in order to carry out endoscopic submucosal dissection (ESD) safely and with patients' satisfaction. METHODS:Three hundred sixty-six patients with an early-stage neoplasm of the digestive tract were enrolled. The BIS monitor (A-1050: Aspect medical systems/NIHON KOHDEN, Tokyo, Japan) was used. The appropriate sedative condition was set at 55 to 75 BIS levels (BIS value) during the endoscopic procedures. RESULTS:Among 366 cases, 13 were accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…En adultos, aunque hay más estudios [18][19][20] , los valores de BIS para permitir realizar una EDA en respiración espontánea y con sensación de bienestar del paciente son mayores: solo el 7% de los pacientes de Lera dos Santos et al 18 precisan un BIS menor de 65; el valor medio de BIS en el trabajo de Jang et al 20 para realizar colangiopancreatoradiografía endoscópica (CPRE) es de 76,5.…”
Section: Discussionunclassified
“…En adultos, aunque hay más estudios [18][19][20] , los valores de BIS para permitir realizar una EDA en respiración espontánea y con sensación de bienestar del paciente son mayores: solo el 7% de los pacientes de Lera dos Santos et al 18 precisan un BIS menor de 65; el valor medio de BIS en el trabajo de Jang et al 20 para realizar colangiopancreatoradiografía endoscópica (CPRE) es de 76,5.…”
Section: Discussionunclassified
“…Zahlreiche weitere Studien [432][433][434][435][436][437][438][439][440][441] konnten mehrheitlich allerdings keine signifikante Verminderung der benötigten Propofol-Dosis im Rahmen meist interventioneller Endoskopien belegen. Auch führte die Anwendung des BIS-Monitorings überwiegend nicht zu einer Reduktion von Surrogat-Parametern der Patientensicherheit (Hypoxämie, RR-Abfall) [436].…”
Section: Räumliche Und Apparative Ausstattungunclassified
“…Since colorectal ESD is a highly complex endoscopic technique and sometimes needs long periods of time to be performed, conscious sedation is the standard care for the majority of ESD. Although few publications focus on anesthesia especially for colorectal ESD, Hata et al [22] reported that an intravenous drip infusion of pentazocine and propofol was used to maintain the sedative condition on early-stage tumors of digestive tract. Bispectral index (BIS), which re ecting the hypnotic e ects of anesthetic drugs on the central nervous system, was measured by a BIS monitor, and Hata et alsuggested that a BIS value between 70 to 75 is suitable for safe ESD.…”
Section: Preoperative Preparation Of the Patientsmentioning
confidence: 99%